Microbiome and cancer: from mechanistic implications in disease progression and treatment to development of novel antitumoral strategies - Constantin, Marian; Chifiriuc, Mariana Carmen; Mihaescu, Grigore; Corcionivoschi, Nicolae; Burlibasa, Liliana; Bleotu, Coralia; Tudorache, Sorin; Mitache, Magda Mihaela; Filip, Roxana; Munteanu, Simona-Gloria; Gradisteanu Pircalabioru, Gratiela (Frontiers in Immunology, 2024)
Cancer is a very aggressive disease and one of mankind's most important health problems, causing numerous deaths each year. Its etiology is complex, including genetic, gender-related, infectious diseases, dysbiosis, immunological imbalances, lifestyle, including dietary factors, pollution etc. Cancer patients also become immunosuppressed, frequently as side effects of chemotherapy and radiotherapy, and prone to infections, which further promote the proliferation of tumor cells. In recent decades, the role and importance of the microbiota in cancer has become a hot spot in human biology research, bringing together oncology and human microbiology. In addition to their roles in the etiology of different cancers, microorganisms interact with tumor cells and may be involved in modulating their response to treatment and in the toxicity of anti-tumor therapies.In this review, we present an update on the roles of microbiota in cancer with a focus on interference with anticancer treatments and anticancer potential.